Synthesis and Physicochemical Characteristics of 6,6-Difluorobicyclo[3.2.0]heptane Derivatives - Bohdan L. Moroz; Serhii M. Holovach; Kostiantyn P. Melnykov; Dmytro S. Lesyk; Andriy A. Filatov; Oleksandr O. Grygorenko (Журнал органічної та фармацевтичної хімії)
The gram-scale synthesis of 6,6-difluorobicyclo[3.2.0]heptane-derived building blocks (i.e., primary amine and carboxylic acid) was performed via the deoxofluorination of the corresponding bicyclic keto ester with diethylaminosulfur trifluride (DAST). Physicochemical properties of the compounds obtained (i.e., pKa) or their model benzamide / anilide derivatives (i.e., LogP) were determined experimentally and compared to those of monocyclic and non-fluorinated bicyclic counterparts. It was found that gem-difluorination expectedly decreased the pKa values by 0.3 - 0.5 units, whereas the LogP values were decreased by 0.54 - 0.55 units. Meanwhile, the bicyclic system itself had a negligible impact on the compounds’ acidity and lipophilicity compared to the monocyclic counterparts.